Synthesis and characterisation of TiAl/Al2O3 for high-temperature applications - Ranjith, Shravan (My University, 2022)
There is an increasing demand for new materials to improve engine efficiency and keep up with the regulations in the aerospace sector. The titanium aluminide (TiAl) has been a material of interest mainly because of the properties such as low density, high stiffness, and high creep resistance. In addition, aluminium oxide (Al2O3) as reinforcement particles allows to improve corrosion resistance and mechanical properties. Metal matrix composites (MMCs) can attain superior mechanical and thermal properties because of the reinforced matrix. These materials could be processed by surface coating on low value parts as well, extending its pool of applications to marine, chemical and other applications. In this master thesis, the synthesis of TiAl/Al2O3, titanium metal matrix composite material from titanium dioxide (TiO2) and aluminium (Al) will be investigated. Ball milling and synthesis at high temperature have been employed to attain the phase transformation to TiAl/Al2O3. During synthesis, the effect and influence of argon (Ar) and hydrogen (H2) atmospheres on the final composite was studied. Oxygen analysis and thermogravimetric analyses were used to follow material synthesis in this study. X-ray diffraction peaks confirmed the phase transformation from TiO2 and Al to TiAl/Al2O3. The final particle morphology was characterised using scanning electron microscopy (SEM) and light optical microscopy (LOM).
Keywords: Titanium aluminide; Aluminium oxide; Ball milling; Metal powder; High temperature synthesis; Processing atmosphere